2010
DOI: 10.1080/00224490903161639
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalence in Adolescents' Decisions about Having Their First Sexual Intercourse

Abstract: This study, based on sexual script theory, assessed ambivalence in the decision to have sexual intercourse for the first time in 687 adolescents. On average, adolescents showed moderate levels of ambivalence. Younger adolescents, students from the highest school track, adolescents with less positive body image, those with higher love attitudes, those who did not take the initiative to have intercourse, and those feeling pressured to have sex showed higher levels of ambivalence during their decisions. Higher le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Adolescents who are less prepared for intimate relationships nonetheless may feel age-normative pressure to be sexually active (Tolman & McClelland, 2011) and may use acohol to facilitate sexual activity outside of an intimate relationship (Livingston, et al, 2013). Lack of preparedness for intimacy or sex may also explain why individuals in the AI group were older at first coitus since these factors are associated with later coital initiation (Pinquart, 2010). An underlying mechanism, such as psychosocial maturity or social competence, may account for both of these contextual effects.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents who are less prepared for intimate relationships nonetheless may feel age-normative pressure to be sexually active (Tolman & McClelland, 2011) and may use acohol to facilitate sexual activity outside of an intimate relationship (Livingston, et al, 2013). Lack of preparedness for intimacy or sex may also explain why individuals in the AI group were older at first coitus since these factors are associated with later coital initiation (Pinquart, 2010). An underlying mechanism, such as psychosocial maturity or social competence, may account for both of these contextual effects.…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence that sexuality is a source of ambivalence for adolescents and young adults (e.g., Muehlenhard and Peterson 2005;O'Sullivan and Gaines 1998;Pinquart 2009). If we acknowledge that sexual empowerment can be multidimensional, then we allow for the fact that adolescent girls often may experience ambivalent empowerment.…”
Section: Empowerment and Ambivalencementioning
confidence: 99%
“…The majority of authors that have written about empowerment (generally) and about the sexual empowerment of adolescent girls (specifically) have written from their position in mainstream U.S. culture, and this is also my cultural context. However, some of the theoretical and empirical work cited in this article does come from other countries, including Australia (Bryant and Schofield 2007;Whitehead and Kurz 2009), Germany (Pinquart 2009), the Netherlands van Zoonen 2006, 2007;Vanwesenbeeck 2009), New Zealand (Allen 2008), and the UK (Andrews 2002;Gill 2007;Henwood and Pidgeon 1995;Spencer et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies of young women have reported significant associations between negative body image and risky sexual behaviors, including lower probability of using contraceptives and earlier age of first intercourse (Eisenberg, Neumark-Sztainer, & Lust, 2005;Gillen, Lefkowitz, & Shearer, 2006;Pinquart, 2010). In addition, negative body image is associated with women's sexual functioning: women who experience greater anxiety and shame about their bodies have lower levels of sexual desire and arousability (Koch, Mansfield, Thurau, & Carey, 2005;Sanchez & Kiefer, 2007;Seal, Bradford, & Meston, 2009) and report decreased sexual satisfaction (Weaver & Byers, 2006;Yamamiya, Cash, & Thompson, 2006).…”
Section: Introductionmentioning
confidence: 99%